Analisis Komparatif Kinerja Karyawan Tetap dan Karyawan Tidak Tetap di Bagian Cetak Perum Peruri - Dwiki Abastian; Uus MD Fadli; Laras Ratu Khalida (J-MAS (Jurnal Manajemen dan Sains), 2023)
The company needs to monitor the performance of each employee by conducting regular evaluations on employee performance, so that the company is able to control the high and low performance of the company in order to achieve the goals expected by the company. Research was conducted at Perum Peruri to examine the difference in performance between non-permanent employees and permanent employees whether there are differences in terms of performance and workload. This study aims to test and analyze the difference in the performance of non-permanent and fixed employees in one of the printed parts at Perum Peruri. This type of research is a comparative analysis. The population is all employees in one print section totaling 55 people, consisting of 23 non-permanent employees and 32 permanent employees, the sample is 48 people consisting of 28 permanent employees and from non-permanent employees as many as 20 people calculated using the Slovin formula at an error rate of 5%. The data scale uses differential semantics which then to see the difference in performance of the two groups of employees is carried out anova analysis using one way analysis. The results of this study show that there are 13 indicators that are considered to have the same performance and there are 11 indicators that are considered significantly different, where the performance of non-permanent employees is lower than that of permanent employees. This provides an understanding that there needs to be better coaching on these indicators by the company.